Effectiveness of muscle strengthening in early postoperative total knee arthroplasty: systematic review with meta-analysis - Alany Gabrielli Leite; Beatriz Batista Vicente; Alessandra Madia Mantovani; Allysiê Priscilla de Souza Cavina (Fisioterapia e Pesquisa)
ABSTRACT Total Knee Arthroplasty (TKA) is a surgical intervention, in which the affected joint is replaced by a prosthesis. Physical therapy is essential in rehabilitation after TKA, which can decrease the length of hospital stay, reduce symptoms and improve knee function. This study aimed to analyze the effects of muscle strengthening on the functioning of individuals with TKA in the early postoperative period. Studies were retrieved from the Pubmed, PEDro, LILACS, EMBASE, CINAHL and Cochrane Library databases, using following terms and keywords: Arthroplasties, Knee Replacement, Physiotherapy, Exercise, Rehabilitation and Postoperative. All included studies were assessed for methodological quality, using the PEDro Scale. Only randomized controlled trials involving unicompartmental knee replacement in the early postoperative period were included in this review. All meta-analyses were conducted using the Review Manager - RevMane software described as standardized mean difference (SMD) with 95% confidence intervals (CI). Nine studies were chosen to review the full text. The main findings demonstrated that muscle strengthening, after comparison with other variables, was effective only for the variable muscle strength (two studies, n=155; MD=−1.39, 95% CI [−2.58, −0.19]; p=0,02; I²=96%) improving overall functioning. For the other analyses, however, no significant differences were observed. This study outcomes suggest muscle strengthening-when initiated in the early postoperative period-is better than the comparison conditions in knee functioning.